Maternal serum alpha-fetoprotein screening: report of a Canadian pilot project. - Doran, T A (1987)
A pilot project of maternal serum alpha-fetoprotein (MSAFP) screening was carried out in Ontario from 1982 to 1985 to examine the feasibility and acceptability of screening a prenatal population for open fetal neural tube defects. A total of 8140 patients at low genetic risk were screened. Patient acceptance was excellent. Blood samples were taken at 16 to 18 weeks' gestation. If the MSAFP level was elevated, the assay was repeated and an ultrasound examination performed. Amniocentesis was offered to 67 women with unexplained persistently elevated levels. The outcome of pregnancy was known in 7473 patients (91.8%). Seven of nine known open fetal neural tube defects were detected. All were confirmed, and no unaffected fetuses were aborted on the basis of the screening results. The rates of perinatal death (6.7%), intrauterine growth retardation (11.7%) and prematurity (23.3%) were significantly higher among the patients with unexplained elevated MSAFP levels than among those with normal levels (p less than 0.001). Of 20 patients with unexplained low levels, 10 subsequently had spontaneous abortions and 10 gave birth to term appropriate-for-gestational-age infants. Seven of nine patients who gave birth to infants with autosomal trisomy had MSAFP values below the median. The findings indicate that MSAFP screening is feasible, accurate and acceptable in a low-risk area.